1998
DOI: 10.1259/bjr.71.843.9616246
|View full text |Cite
|
Sign up to set email alerts
|

Cervical ecchordosis physaliphora: CT and MR features.

Abstract: We report a case of cervical ecchordosis physaliphora in an elderly man who presented with hemihypoaesthesia and contralateral hemiparesis. MRI showed a well defined, non-enhancing extradural mass lesion on the dorsal surface of the odontoid process of the axis. The lesion was of intermediate signal intensity on T1 weighted images and of low signal intensity on T2 weighted images. CT showed a small bony defect on the adjacent cortex of the odontoid process. Recognition of the imaging features of ecchordosis ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…2,6,21,23,24,26,27,37 These histological qualities lend to their iso-to hypointensity on T1-weighted MRI and hyperintensity on T2-weighted MRI. 6,22,23,34,35 However, EP demonstrates no contrast enhancement, unlike chordomas, which usually enhance and are more often located extradurally. 3,21,35 These are helpful features in making the distinction between the two lesions.…”
Section: Discussionmentioning
confidence: 99%
“…2,6,21,23,24,26,27,37 These histological qualities lend to their iso-to hypointensity on T1-weighted MRI and hyperintensity on T2-weighted MRI. 6,22,23,34,35 However, EP demonstrates no contrast enhancement, unlike chordomas, which usually enhance and are more often located extradurally. 3,21,35 These are helpful features in making the distinction between the two lesions.…”
Section: Discussionmentioning
confidence: 99%
“…They are often located intracranially, on the dorsum of the clivus and in the prepontine cisterna [13]. They can be found at any level from the dorsum sellae to the saccrococcygeal region and are usually present extradurally [13]. Ecchordoses grow slowly and in most cases are clinically asymptomatic [7].…”
Section: Discussionmentioning
confidence: 99%
“…Ecchordoses grow slowly and in most cases are clinically asymptomatic [7]. Some rare cases do become symptomatic trough tumour expansion, brain compression or haemorrhage [13]. Because of their location, the differential diagnosis with BNCTs is easy [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of this finding varies between 0.5 and 2% of autopsies [8]. EP is usually asymptomatic and only few authors have reported EP-associated symptoms due to tumour expansion and compression of the surrounding structures [1,12,13].…”
Section: Introductionmentioning
confidence: 99%